Managing Multimorbidity: How Can the Patient Experience be Improved?. Issue 1 (2016) - Hasardzhiev, Stanimir; Mendão, Luís; Nolte, Wolfram; Aben, Bert; Kadenbach, Karin
The patient's experience of their own healthcare is an important aspect of care quality that has been shown to improve clinical and other outcomes. Very little is currently known about patient experience in the management of multimorbidity, although preliminary evidence suggests that it may be poor. Individuals with multimorbidity report better experiences of care when they are knowledgeable and involved in the decision-making, when their care is well coordinated, and communication is good. A greater focus on disease prevention, stronger collaboration between health and social care services, and the provision of more integrated care for people with mental and physical health problems would also help to improve the patient experience. Advocacy groups can amplify the patient voice and improve access to care, as well as provide information and support to patients and their families. Patients have an important role in preventing multimorbidity and improving its management, and should be involved in the development of health policies and the delivery of healthcare services. Inequalities in access to quality healthcare must also be addressed.